INCREASING ABILITY TO SOLVE MATH WORD PROBLEM THROUGH LOGAN AVENUE PROBLEM SOLVING (LAPS-HEURISTIK) LEARNING - Mahmudah, Umi Rofi'atul; Winarni, Retno; Budiharto, Tri (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve the students’ ability to solve math word problem in fifth grade of State Elementary School of Tegalsari No.60 Surakarta in the academic year 2017/2018 through Logan Avenue Problem Solving (LAPS-Heuristic) learning. The data collecting techniques were in-depth interviews, observations, tests, and documentation. The data validating technique were content validity, technique triangulation, and source triangulation. Data analyzing were descriptive comparative analysis and interactive analysis. The results of this class action research showed the achievement of the ability to solve math word problem at fifth-grade students of Tegalsari State Elementary School No.60 Surakarta academic year 2017/2018. The classical completeness of students’ score to solve math word problem has increased, from 33,33% in pretest to 57,14% in cycle I, and 85,71% in cycle II. The conclusion of this research is the use of LAPS-Heuristic learning can improve the students’ ability to solve math word problem in fifth-grade of State Elementary School of Tegalsari No.60 Surakarta academic year 2017/2018.